On the Dangerous Game of Collaborating with Nazis: An Historico-Socio-Legal Reconstruction of that Forgotten Past Located within Silence, Absence and [Dis]Connections between Law's History and Critical Legal Scholarship. (2013) - Charlesworth, Lorie
No abstract available